Enacting social transformation through occupation: A narrative literature review. (17th November 2022) - Cunningham, Miranda; Warren, Alison; Pollard, Nick; Abey, Sally
Abstract: Background: In occupational therapy and occupational science there is a drive to confront social and health injustices through occupation-based practices with social transformation as a goal. However, scholars acknowledge a lack of theory to support this developing area of practice. Aim: To explore how occupations have been used to enact social transformation for disadvantaged communities and to elucidate socially transformative outcomes. Methods: A narrative literature review was carried out, focussing specifically on arts-based occupations, using seven databases. Thirty-eight items were included. Results: Three overarching themes emerged: experiences related to giving voice; levels of change and arts-based occupations influence social change. Conclusions: Art forms as a means of expression can support people to make demands for change. This was true whether the art form was adopted at grass roots level, or via formalized projects run by researchers or Non-Government Organizations. Whilst personal change and small scale social change outcomes were achievable, larger scale structural change was not evident. Unintended outcomes in the form of risks to participants were reported. How and why change came about was not clearly articulated; leaving a need for further exploration of the mechanisms and contexts supporting change in the growing field of social transformation through occupation.